Wildlife hunting rights of the aborigines in peninsular Malaysia: a dilemma protecting humans or animals? - Hussain, Faridah; Hamin, Zaiton; Ariffin, Nur Izzati; Alang, Kemala; Rahmat, Nur Ezan; Mohd. Zain, Nor Razinah (Human Resource Management Academic Research Society, 2022)
In Malaysia, the native customary rights of the indigenous people, known as the 'Orang Asli', are rather broad, including fishing, hunting, and foraging that flow from site-specific occupation and livelihood. However, in the modern era, despite the protection of the old pre-independence legislation, the Aboriginal Peoples Act of 1954, the aborigines' exercise of such rights appears to be problematic as the more recent legislations, such as the Wildlife Conservation Act 2010, invoke several restrictions on fishing or hunting in the forest areas occupied by the aborigines. Additionally, most local literature mainly focuses on the aborigines' land rights; consequently, hunting rights have remained under researched. Given the dearth of academic research on this right, this paper examines how the 2010 Act infringes on the aborigines' hunting rights and, broadly, their traditional way of life. This paper adopts a qualitative research methodology, employing a doctrinal content analysis that would provide a subterranean understanding of the tension between the legal protection of wildlife and the aborigines' rights in Malaysia. The findings revealed that the native rights and social interests of the aborigines are mainly ignored, overlooked, and appear to be superseded by the interests of wildlife animals.